An Estimation Method for the Viscosity of Dissolved Waxy Lube Oils in MEK-Toluene Solvent Composition - Al-Kayiem, Hussain H. (2013)

(untitled)
This paper presents a general inspection method of the dynamic viscosity of lubricating oil feedstock dissolved in MEK/toluene in solvent dewaxing process, where the higher normal paraffin components are to be extracted. A reliable technique to determine the flow properties in the complex multi-components mixture depends on selection of higher carbon number as a solute and light one as a liquid that matches the wax mass fraction in the light portion of the oil. The study focuses on the viscosity in the dissolution region (liquid phase) as a starting point to characterize the solution behavior. The tested feed stock is ASE 30 and the solvent is MEK-Toluene. The selected high carbon numbers are C33, C34, and C45, while the light one is C10. The obtained viscosity results by the proposed method were found to be in good agreement with the predicted viscosities of multi mixture components using the available mixed rules in the literature. The results showed that the proposed solubility model could govern the characteristics of the lubricating base stock oil in dissolution region based on the selected carbon number.